Facile Synthesis of N‐doped TiO2 and Its Enhanced Photocatalytic Activity for Degrading Colorless Pollutants. Issue 5 (19th March 2014) - Xie, Mingzheng; Feng, Yujie; Luan, Yunbo; Fu, Xuedong; Jing, Liqiang
Abstract N‐doped nanocrystalline TiO2 is synthesized successfully through a simple ammonia‐modified hydrolysis‐solvothermal process. It is demonstrated that the resulting TiO2 doped with an appropriate amount of N exhibits high visible photocatalytic activities for the degradation of gas‐phase acetaldehyde and liquid‐phase phenol, which is attributed to its increased visible adsorption, appropriate crystallinity, and good dispersibility, whereas its UV activity is decreased. On the basis of the atmosphere‐controlled surface photovoltage spectra, it is found that the doped N species can capture the photogenerated holes so as to be favorable for photogenerated charge separation, so it is suggested that its decreased UV activity results from its weak adsorption of O2 compared with that of undoped TiO2, as shown by the O2 temperature‐programed desorption curves. Interestingly, the photocatalytic activity of the resulting N‐doped TiO2 under visible or UV irradiation can be improved further by promoting O2 adsorption after modification with an appropriate amount of phosphoric acid.